AN ANALYSIS OF RISK-RETURN CHARACTERISTICS AND RISK EXPOSURES OF VARIOUS HEDGE FUND STRATEGIES - Xiong, Danna (2006)
Hedge funds claim to provide significant diversification for traditional portfolios in attempt to offer attractive returns. This paper provides a comprehensive analysis of the risk-return characteristics, risk exposures of various hedge fund strategies using a database on Barclay Trading Group indices, and examines the return and diversification benefits of hedge fund investing from 1997 to 2006. One of the key characteristics of hedge fund is that it has a low correlation with the market and suggests methods of analysis for dealing with the fact that correlation is unstable. This research uses the simple linear regressions of monthly hedge fund excess returns on monthly S&P 500 excess returns, and this regressions show only modest market exposure and positive added value. Furthermore, the simple nonlinear regressions also applied with both down- and up-market. Different market condition, in this regression, illustrates dissimilar market exposure. Before conclusion, this paper points out that this type of analysis can produce misleading results. Because many hedge funds hold, to various degrees and combinations, illiquid exchange-traded securities or difficult-to-price over-the-counter securities, and hedge funds often price these securities using either last available traded prices or estimates of current market prices for the purposes of monthly reporting. These practices can lead to reported monthly hedge fund returns that are not perfectly synchronous with monthly S&P 500 returns due to the presence of either stale or managed prices.